Contemporary Religion and Culture: Hijra Phenomena - Zulaiha, Eni; Goffary, Irfan; Sucipto, Imam; Hanifah, Hanifah; Ghazali, Adeng Muchtar (International Journal of Psychosocial Rehabilitation, 2020)
The diversity of cultures, customs, and understandings in Indonesia is seen to be complex in a religious context. This study is aimed at describing the phenomenon of hijrah as a contemporary religious phenomenon. This research which applied a descriptive qualitative method by using Jacques Lacan’s psychoanalysis took place at Al Lathif Mosque Bandung where the hijrah youth movement conducted its dakwa activities. The findings showed that the youth hijrah movement is a new fundamentalism movement that uses young people language through new religious symbols. The implication of this research resulted at the emergence of a new religious typology that is more suitable for young people.